The pathogenicity test of blast disease on its alternative host / Nurul Nazwa Azaman - Azaman, Nurul Nazwa (Faculty of Plantation and Agrotechnology, 2018)
Rice is one of the main staple foods consumed by many people especially people in Asia countries and the demand for rice is increasing year by year due to the growing population. The blast diseased is caused by Pyricularia oryzae, an acomycete fungus. Somehow, the P.oryzae can thrive well in different wild weed hosts such as Eleusine indica, Leptochloa chinensis, Echinochloa colona and staple crop, Zea mays. The study was to investigate the P. oryzae isolates ability to infect grasses weed and staple crop through pathogenicity test. The inoculation was done by using approximately 0.5 cm of cultured fungus agar. The agar was placed onto the injured part of a leaf and then was covered using moist cotton. All treatments were inoculated using the same method. Symptoms of the blast were identified after five days inoculation, and length of lesions was measured. The pathogenicity test showed that P. oryzae is pathogenic to all treatments, which are O. sativa, L. chinensis, E.colona, E. indica and Z. mays but with different susceptibility rate. The susceptibility of each host was identified using Standard Screening Scale by IRRI. According to IRRI, L. chinenis is highly susceptible with a scale of nine, meanwhile, E. colona and E. indica is susceptible with the scale of six and seven and Z. mays is moderately susceptible with the scale of four.